Zinc-doped curcumin carbon dots promote infected wound healing with photodynamic via the VEGF signaling pathway - Yifan Zhao; Jia Liu; Lingxiang Sun; Haiyan Liu; Xi Chen; Xuedong Deng; Yilin Ping; Wenze Han; Jing Wang; Feng Tian; Jingyu Yan; Xiuping Wu; et al. (Journal of Nanobiotechnology)
Abstract Management of bacterial infected wounds remains challenging due to the open, susceptibility to infection and delayed healing characteristics of damaged wounds, and there is an urgent need for non-antibiotic-based wound healing strategies. Here, we describe zinc-doped curcumin carbon dots (CCDs) as a novel nanoscale photosensitizer, which was applied in photodynamic therapy (PDT) to promote infected wound healing by modulating various cellular functions. The PDT generation of reactive oxygen species (ROS) effectively inactivates the source of infection without drug resistance, effectively inhibiting the propagation of bacteria and the spread of inflammation in the wound. In addition, CCDs have the ability to promote cell proliferation and extension, accelerate blood vessel formation and collagen deposition, and significantly improve wound healing efficiency by modulating the VEGF signaling pathway. These features create a favorable environment for skin regeneration and synergistically accelerate infected wound healing. We believe it has great potential to address antibiotic misuse and effectively manage infected wounds. Graphical Abstract